South Africa : The Financial Sector-Sovereign Nexus - Hesse, Heiko (IMF Working Papers; Working Paper ;, 2022)
Globally, financial institutions have increased their holdings of domestic sovereign debt, tightening the linkage between the health of the financial system and the level of sovereign debt, or the "financial sector-sovereign nexus," during the ongoing COVID-19 pandemic. In South Africa, the nexus is still relatively moderate, albeit rising, and the increased focus of the Prudential Authority on the associated risks provide reassurance. Options to mitigate such risks through the use of regulatory measures can be explored. However, absent the necessary fiscal consolidation and structural reforms, risks from the nexus to both the financial system and the sovereign will increase.